Answer:
(x+2)(2x-1)
Explanation:
I used a little guess and check for this so bear with me :P
The final answer would always have to be two brackets with x and the relevant variables.
2x²: You know the possible factors that can be multiplied together would be 2x and x. Each factor would have to be in different brackets, so we get (x + smth else)(2x +smth else)
When factorising quadratic expressions, you need to find the correct pair of factors, that when multiplied together, becomes (-2). They also need to become 3x when they are multiplied with the term in the bracket (either x or 2x) and then added together.
Possible factors:
1. 1 × (-2) = (-2)
2. -1 × 2 = (-2)
Assume (x+1)(2x-2) = 2x² -2x +2x -2
= 2x² +0 - 2 (Wrong)
Assume (x-2)(2x+1) = 2x² +x -4x -2
= 2x² -3x -2 (Wrong)
Assume (x-1)(2x+2) = 2x² +2x -2x -2
= 2x² +0 - 2 (Wrong)
Assume (x+2)(2x-1) = 2x² -x +4x -2
= 2x² +3x -2 (Correct!)
Thus, (x+2)(2x-1) is the answer.